Selection of metabolic pathways for continuous hydrogen production under thermophilic and mesophilic temperature conditions in anaerobic fluidized bed reactors - Ferreira, Tiago Borges; Rego, Gabriel Catucci; Ramos, Lucas Rodrigues; Soares, Lais Americo; Sakamoto, Isabel Kimiko; Oliveira, Lorena Lima de [UNESP]; Amancio Varesche, Maria Bernadete; Silva, Edson Luiz (Elsevier B.V., 2018)
This study evaluated the influence of hydraulic retention time (HRT) on hydrogen (H2) production in anaerobic fluidized bed reactors at mesophilic (30 degrees C, AFBR-M) and thermophilic (55 degrees C, AFBR-T) temperatures. Reactors were fed sucrose-based synthetic wastewater (5000 mg chemical oxygen demand . L-1) in the HRT of 8, 6, 4, 2, or 1 h. H-2 production rate increased from 67.8 14.8 to 194.9 57.0 ml H-2.h(-1) L (AFBR-T) and from 72.0 +/- 10.0 to 344.4 +/- 74.0 mL H-2 h(-1) .l(-1) (AFBR-M) when HRT decreased from 8 to 1 h. Maximum H-2 yields for AFBR-T and AFBR-M were 1.93 t 0.21 and 2.68 0.48 mol H-2 mol(-1) sucrose, respectively. The main metabolites were acetic acid (31.3%-41.5%) and butyric acid (10.2%-20.7%) (AFBR-M) and acetate (20.1%-39.3%) and ethanol (14.3%-29.9%) (AFBR-T). Denaturing gradient gel electrophoresis profiles revealed selective enrichment of microbial populations responsible for H2 production by the aceto-butyric route (AFBR-M) and ethanol type fermentation (AFBR-T). (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Biohydrogen; Temperature effect; Mesophilic; Thermophilic; HRT; DGGE